Cardiovascular magnetic resonance for early detection of late cardiotoxicity in asymptomatic survivors of hodgkin and non-hodgkin lymphoma. (13th July 2021) - Van Der Velde, N; Janus, CPM; Bowen, DJ; Hassing, HC; Kardys, I; Van Leeuwen, FE; So-Osman, C; Nout, RA; Manintveld, OC; Hirsch, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Long-term survivors of Hodgkin (HL) and non-Hodgkin (NHL) lymphomas experience late adverse effects of mediastinal radiotherapy and/or anthracycline containing chemotherapy, which lead to premature cardiovascular morbidity and mortality. It is unknown whether early stages of myocardial dysfunction and heart failure in these survivors can be detected by cardiovascular magnetic resonance imaging (CMR). Purpose: To identify early sensitive markers for the detection of subclinical late cardiotoxicity using CMR in asymptomatic survivors of HL and (primary mediastinal large B-cell lymphoma) NHL. Methods: For this prospective observational study, we included 80 HL or selected NHL survivors, who have been free of disease for ≥5 years and were treated with mediastinal radiotherapy (RT) with/without chemotherapy. Patients with known cardiac disease were excluded. Included patients were compared to 40 age- and sex matched healthy controls. CMR included 1) cine imaging for assessment of left ventricular (LV) and right ventricular (RV) dimensions, systolic function and strain; 2) 2-dimensional late gadolinium enhancement (LGE) imaging; 3) T2 mapping and 4) pre- and post-contrast T1 mapping (MOLLI) for assessment of native T1 values and extracellular volume (ECV). Results: Of the 80 patients, 78 (98%) had a history of HL and 2 (2%) of NHL with a mean age of 47 ± 11 years (46% male). All patients were treated with mediastinal RT which was combined with anthracycline containing chemotherapy in 68 (85%) patients. The median interval between diagnosis and CMR was 20 [14 – 26] years. Differences in CMR characteristics between patients and healthy controls are shown in the table. LV end-systolic volume was statistically significantly higher, but LV ejection fraction and mass were significantly lower in patients compared to healthy controls. RV volumes were significantly lower in patients, but RV ejection fraction was preserved. Strain parameters of the LV, i.e. global longitudinal strain, global circumferential strain and global radial strain, were slightly but significantly reduced in patients. No significant differences were found in myocardial T2 times and ECV; however, native myocardial T1 time was significantly higher in patients compared to healthy controls. LGE was detected in 25% of the patients and in the majority of patients with LGE this was classified as hinge point fibrosis. Conclusion: Asymptomatic survivors of HL and NHL are not exempt of late cardiotoxicity, which can be detected by subtle changes in LV myocardial function, strain and native T1 value with CMR. Furthermore, late gadolinium enhancement was present in 25% of the patients. Further longitudinal studies are needed to assess the implication of these changes in relation to clinical outcome.